Rethinking Fiscal Policy in Oil-Exporting Countries - Mirzoev, Tokhir (IMF Working Papers; Working Paper ;, 2019)
We examine the existing fiscal policy paradigm in commodity-exporting countries. First, we argue that its centerpiece-the permanent income hypothesis (PIH)-is not consistent with either intergenerational equity or long-term sustainability in the presence of uncertainty. Policies to achieve these goals need to be more prudent and better anchored than the PIH. Second, we point out the presence of a volatility tradeoff between government spending and wealth and re-assess long-held views on the appropriate fiscal anchors, the vice of procyclicality, and the (im)possibility of simultaneously smoothing consumption and ensuring intergenerational equity and sustainability. Finally, we propose what we call a prudent wealth stabilization policy that would be more consistent with long-term fiscal policy goals, yet relatively simple to implement and communicate.